Model Penanggulangan Kemiskinan Berbasis Aset Masyarakat di Kecamatan Jatinangor - Resnawaty, Risna; Fedryansyah, Muhammad (Social Welfare Study Program, 2016)
The pattern of top-down development often create new problems for society, among others, issues of poverty that occurred in the area of education Jatinangor. The local community were marginalized by the regional changes. Agriculture areas which is the place for working has transformed into educational and residential areas. The change didn’t considering the ability of society to change in accordance with the expected development. Various programs of addressing poverty has been done by the government but the level of unemployment and poverty in the region Jatinangor not significantly reduced. The low level of education of the community in reality that is ironic for an area which has five colleges of higher education. To overcome these problems, Community development is one strategy for urban poverty reduction, Jatinangor has community-owned assets as capital that can be used to reduce the problems of poverty. There are two important issues relating to existing assets include “optimalization” strategy purposes to improve the functioning of the asset in improving the quality of life and solving problemsof poverty, as well as the “revitalization” strategy purposes to improve existing assets or deemed less support or be the ause of the problem of poverty itself.Keywords: Community Development, Assets Based Community Development, Poverty Reduction.